IMPLEMENTASI DAKWAH MAHASISWI AL-HIKMAH DI MASYARAKAT - Misroji; Gita Amelia (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This study aims to analyze the implementation of da'wah carried out by STIDDI Al-hikmah Jakarta students. The research method used is qualitative. This research includes research with a field approach. The method of data collection was done by descriptive questionnaire, documentation, and literature. The data analysis method used is descriptive qualitative Miles and Hubberman. The research finding is that the implementation of da'wah by STID DI Al-Hikmah students is carried out in the form of da'wah bil verbal/speech, da'wah bil qalam/written and da'wah bil things/deeds. Bi-oral da'wah activities carried out by STID DI Al-Hikmah students are teaching religious knowledge, reminding and giving advice, discussion/sharing, halaqoh coaching, being a speaker, mentoring spiritualists, filling out studies/recitations, also by utilizing social media by becoming a broadcaster/da'wah. through the online application, Podcasts.